2018
DOI: 10.15421/011824
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of poultry ectoparasites in industrial farms, farms, and private plots with different rearing technologies

Abstract: One of the problems in growing and keeping poultry, both in industrial and farm and kitchen garden environments is ectoparasites, which are responsible for lowering the productivity of poultry and causing economic losses. The study of the prevalence and diagnosis of bird ectoparasites on poultry farms with different maintenance technologies is important for the further development of integrated methods for combating them. Our research was conducted during 2006–2017 in 16 regions of Ukraine and the Autonomous R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The high number of lice species recovered from chickens that perch around as well as those in household dwellings and wooden cages as opposed to those kept on bare floor could be because housing structures provide shelter for ectoparasites and also complicate efficient cleaning of poultry houses. A similar finding was put forward by Paliy et al, (2018) where a high number of chicken mite was recovered from wooden coops. This study also revealed that majority of poultry keepers (99.3%) had prior knowledge of ectoparasites.…”
Section: Discussionsupporting
confidence: 79%
“…The high number of lice species recovered from chickens that perch around as well as those in household dwellings and wooden cages as opposed to those kept on bare floor could be because housing structures provide shelter for ectoparasites and also complicate efficient cleaning of poultry houses. A similar finding was put forward by Paliy et al, (2018) where a high number of chicken mite was recovered from wooden coops. This study also revealed that majority of poultry keepers (99.3%) had prior knowledge of ectoparasites.…”
Section: Discussionsupporting
confidence: 79%
“…The problem of parasitic diseases of agricultural and domestic animals remains relevant today (Paliy et al, 2018a;2018b;2018c;, despite the introduction of new high-performance anthelminths (Lloyd et al, 2000;Lambertz et al, 2019;Preston et al, 2019) and disinfectants (Paliy et al, 2015;2020a;Stegniy et al, 2019;Bondarchuk et al, 2019). Most recently, the results of advanced studies of ostrich parasites (Struthio camelus), mainly from European countries where commercial ostrich farming is gaining momentum (Cooper, 2005) have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic diseases of agricultural and domestic animals are still an urgent problem in veterinary medicine, the solution of which requires a comprehensive, scientifically grounded, innovative approach (Abou-El-Naga, 2018;Paliy et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%